Transformative Role of Nuclear Technologies in the Healthcare System of Pakistan: Advancements and Impact - Shazia Fatima (CISS Insight Journal, 2025)
Nuclear technology and techniques have become the foundation of modern medicine, revolutionizing the diagnosis, treatment, and management of various pathologies and disease processes. The healthcare sector in Pakistan has also witnessed transformative developments, especially in the fields of oncology, cardiology, and neurology, among others, contributing directly to the United Nations (UN) Sustainable Development Goal 3 (SDG 3). Pakistan, from the outset, has continued to invest in healthcare facilities and developed a comprehensive network of 51 nuclear medicine facilities and 49 oncology centers, including 19 Atomic Energy Cancer Hospitals (AECHs). These centers offer state-of-the-art diagnostic and therapeutic services, including hybrid imaging with Positron Emission Tomography/Computed Tomography (PET/CT), Single Photon Emission Computed Tomography/Computed Tomography (SPECT/CT), conventional gamma cameras, Computed Tomography (CT), Magnetic Resonance Imaging (MRI) mammography, and radiation treatment with teletherapy machines like linear accelerators, gamma and cyberknife, brachytherapy units as well as trailblazing theragnostic technologies. The production of indigenous radiopharmaceuticals, radioisotopes, and in-house cyclotron-based isotopes production has upgraded nuclear medicine facilities, including hospitals and diagnostic centers, by promoting self-reliance and reducing healthcare costs. In this regard, the Pakistan Nuclear Regulatory Authority (PNRA) ensures safety and standardization across these facilities through its regulatory framework and legislation. Although Pakistan has successfully established a comprehensive infrastructure of healthcare facilities using nuclear techniques, these facilities, primarily concentrated in major cities, are insufficient for its 250 million population. To overcome this challenge, there is a need for continued capacity building through infrastructure development, human resource training, and enhanced local isotope production. This article discusses Pakistan’s historical developments in the field of healthcare, its current infrastructure, socioeconomic impact, and strategic direction of nuclear medicine and radiotherapy. This article further highlights the transformative role of nuclear technologies in improving public health outcomes and national healthcare resilience.